5y-1+y+29=6y+40-4y

Simple and best practice solution for 5y-1+y+29=6y+40-4y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y-1+y+29=6y+40-4y equation:


Simplifying
5y + -1 + y + 29 = 6y + 40 + -4y

Reorder the terms:
-1 + 29 + 5y + y = 6y + 40 + -4y

Combine like terms: -1 + 29 = 28
28 + 5y + y = 6y + 40 + -4y

Combine like terms: 5y + y = 6y
28 + 6y = 6y + 40 + -4y

Reorder the terms:
28 + 6y = 40 + 6y + -4y

Combine like terms: 6y + -4y = 2y
28 + 6y = 40 + 2y

Solving
28 + 6y = 40 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
28 + 6y + -2y = 40 + 2y + -2y

Combine like terms: 6y + -2y = 4y
28 + 4y = 40 + 2y + -2y

Combine like terms: 2y + -2y = 0
28 + 4y = 40 + 0
28 + 4y = 40

Add '-28' to each side of the equation.
28 + -28 + 4y = 40 + -28

Combine like terms: 28 + -28 = 0
0 + 4y = 40 + -28
4y = 40 + -28

Combine like terms: 40 + -28 = 12
4y = 12

Divide each side by '4'.
y = 3

Simplifying
y = 3

See similar equations:

| 1x-1+x/3=x/x-1 | | 4x+6-6=-6+6 | | 27-x=14 | | 4x+37=11x-3 | | 1/9+y=5/18 | | y/5=10/25 | | 6x-12=9x-27 | | 7.5/6 | | -2(x+1)+13x=12 | | (3x-5)+(2x+10)=4x+2 | | 2x+6-6=-4-6 | | Y/6=29 | | y-8=5(x+8) | | 5(4x-5)= | | 1+10x=46x | | -7(x+1)-18=34+4 | | 51-2x=12-10x | | (-8*-8)+3x=5x+4*4*4 | | 9ln(4x)=72 | | 1/2x^2-2x+3=0 | | 2+6/2+6=4 | | 0.01x+0.10x+0.25(33-2x)=2.01 | | 4+3*4+5*2=64 | | 8T+10=5T-8 | | (0.5t-2)(0.4t+6)=0 | | 0.01x+0.10x+0.25(45-2x)=3.84 | | 14x-38=8x | | 15y-713y=17 | | 1/5(x+5)=7 | | X-3/3=x+5/7 | | 28.95(3)+.31x=150 | | 5-30a/5= |

Equations solver categories